Molecular sexual determinants in Pistacia genus by KASP assay - AYDİN, YILDIZ; ALTINKUT UNCUOĞLU, AHU (My University, 2022)
Background Pistacia is a genus of dioecious plant species whose trees can take 4-5 years to reach the economically valuable fruit-bearing stage. The fruits have great importance as raw material in the food, healthcare, and baking industries. For that reason, the identification of individual plants in the early juvenile period for the pollination and positioning of trees is crucial for growers. The objective of this study is to develop markers for each Pistacia species that can help in screening the sex of plant seedlings before they reach the reproductive stage, without waiting for morphological characteristics to appear. Methods and results Within this context, by using the power of the kompetitive allele-specific PCR (KASP) assay technology as a marker screening system, we successfully discriminated seven out of eight Pistacia species: P. atlantica, P. integerrima, P. khinjuk, P. mutica, P. terebinthus, P. vera, and P. lentiscus. We used a high-throughput DNA sequence read archive (SRA) to assemble a reference genome that was employed in our studies as a de novo bioinformatics method. Four genomic regions from SRA and three single-nucleotide polymorphism (SNP) positions from Kafkas et al. BMC Genomics 16:98, 2015) were selected and sequenced with collected plant material from predominantly the Antepfistigi Research Institute Collection Garden, and eight species were aligned intraspecifically for SNP mining. In total, 12 SNP markers were converted to KASP markers, and 5 of them (SNP-PIS-133396, SNP-PIS-167992, P-ATL-91951-565, P-INT-91951-256, P-KHI-91951-115) showed clear allelic discrimination between male and female plants. SNP-PIS-167992 and P-ATL-91951-565 were identified as the best marker assays because they showed allelic frequency differences for all individuals and for both homozygous and heterozygous characters. These markers could be the most comprehensive ones for the whole genus because they showed discriminative power for several species. Conclusions This study is the first one to use the KASP assay for sex discrimination in Pistacia species, and it can be regarded as a precursor study for sex discrimination by KASP for plants in general.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Moleküler Biyoloji ve Genetik; Yaşam Bilimleri (LIFE); BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); Biochemistry, Genetics and Molecular Biology (miscellaneous); Clinical Biochemistry; Cancer Research; Molecular Biology; Drug Discovery; Aging; General Biochemistry, Genetics and Molecular Biology; Biochemistry; Structural Biology; KASP; Pistacia; Sex discrimination; SNP; SINGLE NUCLEOTIDE POLYMORPHISMS; GENETIC DIVERSITY; MARKERS; RESISTANCE; IDENTIFICATION; PCR; L.